Designing a framework for blockchain-based e-voting system for Libya - Salem S. M. Khalifa; Ali Mohamed E. Ejmaa; Abdulmawla Mohammad Ali Najih; Mohamed Abd Arahman Masoud Zneen (Institute of Advanced Engineering and Science, 2023)
A transition to democratic rule is considered the first step down a long road towards Libya’s recovery and prosperity. Thus, it strives to improve the country’s elections by introducing new technologies. A blockchain is a distributed ledger that is characterised by independence and security. Therefore, it has been widely applied in various fields ranging from credit encryption and digital currency. With the development of internet technology, electronic voting (E-voting) systems have been greatly popularised. However, they suffer from various security threats, which create a sense of distrust among existing systems. Integrating blockchain with online elections is a promising trend, which could lead to make an election transparent, immutable, reliable, and more secure. In this paper, we present a literature review and a case analysis of blockchain technology. Moreover, a framework for an E-voting system based on blockchain is proposed. The methodology is adopted on the basis of three activities, they are identification of the relevant literature about E-voting, system modelling, and the determination of suitable technological tools. The framework is secure and reliable. Thus, it could help increase the number of voters and ensure a high level of participation, as well as facilitate free and fair electoral processes